Pharmaceutical and biomedical project management in a changing global environment - Babler, Scott D. (Hoboken, N.J. : Wiley, 2010)
'This book explores some of the critical forces at work today in the complex endeavor of pharmaceutical and medical product development. Applying a structured project management framework enables companies to select and allocate the appropriate people and resources to achieve successful outcomes. The book presents chapters addressing selected issues written by experienced professionals grappling with these problems every day. Such coverage provides real-world examples of contemporary problems and their solutions'--Provided by publisher.
Includes index.
Keywords: Project management; Pharmaceutical industry; Medical instruments and apparatus industry; Drug Industry -- organization & administration; Equipment and Supplies; Health Care Sector -- organization & administration; Personnel Management -- methods; Planning Techniques; Program Development -- methods